Iodine-Catalyzed Oxidative Cross-Dehydrogenative Coupling of Quinoxalinones and Indoles: Synthesis of 3-(Indol-2-yl)quinoxalin-2-one under Mild and Ambient Conditions - Noikham, Medena; Kittikool, Tanakorn; Yotphan, Sirilata (Synthesis, 2018)
A highly efficient iodine-catalyzed oxidative cross-dehydrogenative coupling reaction of quinoxalinones and indoles has been developed. Without the requirement of peroxide and acid, this reaction utilizes a catalytic amount of molecular iodine to facilitate the C–C bond formation under ambient air. This simple and easy-to-handle protocol represents an interesting synthetic alternative with a good scope and functional group compatibility.
Keywords: iodine; quinoxalinone; indole; oxidative coupling; metal-free